KINERJA PEMERINTAHAN DESA DALAM PENYELENGGARAAN PEMBANGUNAN INFRASTRUKTUR (NAGARI GUGUAK TABEK SARJO, KECAMATAN IV KOTO, KABUPATEN AGAM, SUMATERA BARAT) - Shafyra Amani; Didin Muhafidin; Neneng Weti Isnawaty (Universitas Padjadjaran, 2023)
This research stems from the implementation of infrastructure development in Guguak Tabek Sarojo Village, IV Koto Sub-district, Agam District, West Sumatra where several problems were found, including the non-realization of several infrastructure development activities, community needs related to public infrastructure that could not be met and complaints from the public. related to infrastructure development planning which is considered unfair. This problem appears allegedly influenced by the performance of the village administration. The theory used in this study is the theory of performance appraisal of public organizations described by Agus Dwiyanto (2006) which consists of productivity, service quality, responsiveness, responsibility and accountability. The research method applied is qualitative research using interviews, observation, and documentation as data collection techniques. The results of the research that the authors got were that the performance of village government in implementing infrastructure development in Nagari Guguak Tabek Sarojo, IV Koto District, Agam Regency, West Sumatra was not optimal because there were several dimensions of measuring the performance of public sector organizations that could not be fulfilled properly, namely low ability to manage resources (productivity), low ability to develop programs (responsiveness) and low ability to provide services fairly (accountability). Even so, there are dimensions of measuring the performance of public sector organizations that have been fulfilled, including the ability to produce quality (quality of service), the ability to recognize community needs and develop priority scales of activities (responsiveness), and the existence of information disclosure to the public (accountability). The suggestion in this study is that the Village Government needs to improve its ability to develop ideas or ideas innovative for implementation of infrastructure development activities carried out in accordance with community needs and applicable regulations. Penelitian ini bermula dari penyelenggaraan pembangunan infrastruktur di Nagari Guguak Tabek Sarojo, Kecamatan IV Koto, Kabupaten Agam, Sumatera Barat yang ditemukan beberapa permasalahan, diantaranya tidak terealisasikannya beberapa kegiatan pembangunan infrastruktur, adanya kebutuhan masyarakat terkait infrastruktur publik yang belum dipenuhi serta adanya keluhan dari masyarakat terkait perencanaan pembangunan infrastruktur yang dianggap kurang adil. Permasalahan ini muncul diduga dipengaruhi oleh kinerja pemerintahan desa. Teori yang digunakan dalam penelitian ini yaitu teori penilaian kinerja organisasi publik yang dipaparkan oleh Agus Dwiyanto (2006) yang terdiri dari produktivitas, kualitas layanan, responsivitas, responsibilitas dan akuntabilitas. Metode penelitian yang diterapkan ialah penelitian kualitatif dengan menggunakan wawancara, observasi, dan dokumentasi sebagai teknik pengumpulan data. Hasil penelitian yang penulis dapatkan ialah kinerja pemerintahan desa dalam penyelenggaraan pembangunan infrastruktur di Nagari Guguak Tabek Sarojo, Kecamatan IV Koto, Kabupaten Agam, Sumatera Barat belum optimal karena ada beberapa dimensi pengukuran kinerja organisasi sektor publik yang belum dapat terpenuhi dengan baik yaitu rendahnya kemampuan dalam mengelola sumber daya (produktivitas), rendahnya kemampuan dalam mengembangkan program (responsivitas) serta rendahnya kemampuan dalam memberikan pelayanan secara adil (akuntabilitas). Meskipun demikian terdapat dimensi pengukuran kinerja organisasi sektor publik yang sudah terpenuhi diantaranya kemampuan dalam menghasilkan kualitas (kualitas layanan), kemampuan dalam mengenali kebutuhan masyarakat serta menyusun skala prioritas kegiatan (responsivitas), dan adanya keterbukaan informasi kepada masyarakat (akuntabilitas). Saran dalam penelitian ini adalah Pemerintahan Desa perlu meningkatkan kemampuan dalam mengembangkan gagasan atau ide yang inovatif terkait penyelenggaraan pembangunan infrastruktur kegiatan yang dilaksanakan sesuai dengan kebutuhan masyarakat serta regulasi yang berlaku